VD_FINDINFO Jug / 2023 / 202 vom 6. Dezember 2022 - VD Tribunal cantonal (2022)
PRÉSOMPTION D'INNOCENCE, VOLDROIT PÉNAL, CONSTATATION DES FAITS, FIXATION DE LA PEINE, RESPONSABILITÉDROIT PÉNAL, EXPULSIONDROIT PÉNAL, SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE | 139 CP, 19 al. 2 CP, 43 al. 1 CP, 47 CP, 51 CP, 66a bis CP, 10 CPP (CH)